Data exclusivity in pharmaceutical drug products - Demirbaş, Ali (My University, 2007)
ÖNSÖZ İlaç ürünlerindeki veri munhasiriyeti (tekeli), ilaç ürünlerine ilişkin patent, patentlerde süre uzatımı ve pazarda başkaca tekel hakkı tanıyan inhisari nitelikteki koruma tipleri arasında önemli bir yer tutmaktadır. Veri munhasiriyetini, ilaçlara ruhsat ve pazar izni alınması amacıyla mahalli otoriterelere ilk defa verilen ve laboratuar araştırmaları ile insanlar ve hayvanlar üzerinde yapılan test sonuçlarını içeren gizli bilgilerin aynı ilaca ilişkin olarak sonraki başvuru sahipleri tarafından ve mahalli otorite tarafından belli bir süre zarfında sonraki ruhsat ve pazar izni başvurularında kullanılamaması ve o gizli bilgilere referans yapılamaması olarak ifade etmek mümkündür. Bu nedenledir ki, veri münhasiriyeti diğer koruma biçimlerinden olan pazar tekellerinden farklılık arz etmektedir. Zira Avrupa Birliği uygulamasında olduğu gibi veri koruması sona erdikten sonra da pazar koruması devam edebilmektedir. AB’de veri koruması 8 yıl iken Pazar koruması normalde 10 yıldır. Bu demektir ki, sekiz yılın sonunda ikinci başvuru sahibi ilk başvuru sahibinin test ve laboratuar verilerini başvurusunda kullanabilecek ancak 2 yıl daha geçtikten sonra pazara çıkabilecektir. Yine veri koruması patent korumasından da farklılık arz etmektedir. Çalışmanın ilk bölümünde, ilk önce ilaç ürünlerine ilişkin tekeller sonra da veri munhasiriyeti üzerinde genel olarak durulurken, ikinci bölümde veri münhasiriyeti uluslararası düzeyde, Avrupa Birliği, ABD ve Türkiye ölçeğinde daha detaylı bir şekilde ele alınmaktadır.

Data exclusivity in pharmaceuticals is one of the best protection systems among other type of regulatory drug product exclusivities such as patent protection, patent term extension and some other type of marketing exclusivities. Data exclusivity provides the right holder protection on his undisclosed information, in particular the results of tests in humans and animals and clinical trials which are given to the national authorities in order to obtain marketing approval for the drug product for which the application is made. In this regard data exclusivity means that, the second applicant can not use or rely on that data during the exclusive time period in order to obtain marketing approval for the same drug product which was already granted marketing approval first time. Like the second applicant, national regulatory authorities also can not rely on that data in order to grant marketing approval to the second applicant for the same drug product during that exclusive time period. By this reason data exclusivity differs from other type of drug product marketing exclusivities since marketing exclusivity in pharmaceutical drug products may last after data exclusivity time period expires like in the EU system. In the EU normally, while there is 8 year data exclusivity, marketing exclusivity is 10 year. Also data exclusivity differs from patent protection. In part one; firstly the focus is on the regulatory drug product exclusivities and then data exclusivity generally. In part two; data exclusivity is analyzed extensively in international law, in the EU law, in the U.S. law and lastly in Turkish law.
Keywords: Avrupa Birliği Hukuku; İlaç Sanayii_Hukuk